Analisis Pemeriksaan CT Scan Urografi pada Klinis Hidronefrosis di RS Tk Ii Pelamonia Makassar - Miftahul Haq; I Made Lana Prasetya; I Made Adhi Mahendrayana (Syntax Corporation, 2025)
CT Urography is a diagnostic imaging technique used to evaluate the urinary tract system, including the kidneys, ureters, and bladder. This study aims to analyze CT Urography examinations in patients with clinical hydronephrosis at RS TK II Pelamonia Makassar to assess the effectiveness of imaging techniques in detecting obstructions, kidney stones, tumors, and the severity of the condition. The research method used is descriptive qualitative with a case study approach. Data were collected through observations, interviews, and documentation. The study results indicate that CT Urography examination with a slice thickness of 5 mm provides clear visualization of hydronephrosis conditions. The examination procedure at RS TK II Pelamonia Makassar follows standard operating procedures (SOP), although slight differences in imaging parameters were observed compared to theoretical guidelines. In conclusion, CT Urography is an effective imaging modality for detecting hydronephrosis pathology and assists in making more accurate medical decisions.